1998
DOI: 10.1200/jco.1998.16.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of weekly paclitaxel in advanced lung cancer.

Abstract: The MTD of paclitaxel using a weekly schedule is 175 mg/m2/wk for 6 of 8 weeks. Neutropenia limits dosing acutely, but neuropathy is limiting with sustained therapy. This schedule of paclitaxel results in a twofold to threefold increase in dose-intensity with less toxicity than anticipated from conventional dosing. Further evaluation of this schedule is warranted to assess efficacy and toxicity of prolonged administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
55
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 11 publications
0
55
1
Order By: Relevance
“…Historically, response rates of 10% to 15% are seen when using single agent paclitaxel to treat advanced NSCLC (49,50). In contrast, the clinical benefit rate for matuzumab F paclitaxel in our study cohort was significantly higher (f60%), suggesting an additive or synergistic effect of this drug combination.…”
Section: Discussioncontrasting
confidence: 52%
“…Historically, response rates of 10% to 15% are seen when using single agent paclitaxel to treat advanced NSCLC (49,50). In contrast, the clinical benefit rate for matuzumab F paclitaxel in our study cohort was significantly higher (f60%), suggesting an additive or synergistic effect of this drug combination.…”
Section: Discussioncontrasting
confidence: 52%
“…Furthermore, the performance and staging statuses of the study population predicted a major part of the treatment results: the better the performance status and staging status of the study population, the better the response rate and the survival, and also the less severe the treatment toxicities. Weekly paclitaxel treatment has been found to have a higher response rate and better toxicity profiles in many phase II studies of both chemonaïve patients and patients who have failed previous chemotherapy (Akerley et al, 1998;Belani, 2001;Chang et al, 2001;Koumakis et al, 2002). However, there has been no randomised trial comparing weekly paclitaxel plus cisplatin vs other new anticancer drugs plus cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we performed this phase II randomised trial. The weekly dose of paclitaxel single-agent treatment given to the patient can be 90 mg m À2 or higher (with/ without carboplatin or concomitant radiotherapy) (Belani, 2001;Chang et al, 2001;Koumakis et al, 2002), even up to 175 mg m À2 week À1 for 6 of 8 weeks (Akerley et al, 1998). However, there has been no report of a weekly dose of paclitaxel in combination with cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been reported that the weekly short-term (1-or 3-hour) administration of paclitaxel may result in a dramatic increase of the dose-density, at a price of a moderate toxicity (Fennelly et al, 1997;Akerley et al, 1998;Sikov et al, 1998).…”
mentioning
confidence: 99%